PHYLOGENY OF THE WORLD SPECIES OF MUSTHA AMYOT AND SERVILLE (HEMIPTERA: PENTATOMIDAE: PENTATOMINAE: HALYINI) BASED ON MORPHOLOGICAL CHARACTERS - N. Memon; F. Gilbert; A. M. Shaikh (Journal of Animal and Plant Sciences, 2014)
A phylogenetic analysis of all 10 species of the Palaearctic genus Mustha Amyot and Serville is presented here, together with a key. Thirty morphological characters were analyzed using parsimony, including characters of the internal and external male and female genitalia. Using the genus Orthoschizops as an outgroup, only a single most-parsimonious shortest tree resulted. Two species(izmirensis and serratta)were plesiomorphic in the tree. Although only with weak bootstrap support, three distinct clades were evident. A relatively plesiomorphic clade consisted of baranovi, longispinis, gigantea and vicina; the second contained two species, incana and morgani; and the third clade also contained two species, spinosula and spinosus.
Keywords: Phylogeny Mustha; Halyini; Pentatomidae